mOral health in India: Current scenario and future perspectives - O P Kharbanda; Harsh Priya; Upendra Singh Bhadauria; Charu Khurana; Diptajit Das (Wolters Kluwer Medknow Publications, 2019)
Oral diseases affect half of the world's population and found to be the most common and preventable noncommunicable diseases worldwide. The World Health Organization Oral Health Programme work plan 2018-2020 is to prevent the burden of oral diseases using digital technology. With 5 billion mobile phone subscribers in the world, covering over 85% of the world's population, the utilization of technology-based interventions for oral health promotion is no different. In India, numerous medical applications such as eRaktkosh and mDiabetes have been developed for the improvement of general health, whereas few initiatives such as mCessation and National Quitline services for oral health have been undertaken. Digitalization and oral health forms a crucial component in the future of oral health, which should be utilized in ensuring oral health for all.